PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS WEBSITE PADA MATERI BANGUN DATAR SEGITIGA DAN SEGIEMPAT UNTUK SISWA SMP - PERMANA, AGUS AGUNG; RASPATI, SRI DEWI; PERTIWI, DIAN DWI; SABRINA , AMANDA RACHEL (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2024)
This research aims to develop website-based learning media on the subject of triangles and quadrilaterals that are suitable for use in learning in junior high schools. The learning media developed is named TuDi. The type of research conducted is Research and Development (R&D) research using the 4D development model, which consists of 4 stages of activity, namely the definition stage (define), the design stage (design), the development stage (develop), and the dissemination stage (desiminate). The respondents of this research were 32 students of class VIII A of SMPN 238 Jakarta. The results of this research are (1) TuDi learning media is said to be very valid by obtaining a percentage from media experts of 91%, and the results from material and language experts of 94% with an average validity of 93% which is stated as very valid. (2) TuDi learning media is said to be feasible to use by obtaining the results of the teacher and student response questionnaire in the limited test of 96% and the results of the teacher and student response questionnaire in the broad test of 98%, with an average feasibility of 97% which is stated as very feasible. Based on the results of the validation and feasibility trial, it can be concluded that the website-based learning media